If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8u + 1 = 7u + 1 Reorder the terms: 1 + 8u = 7u + 1 Reorder the terms: 1 + 8u = 1 + 7u Add '-1' to each side of the equation. 1 + -1 + 8u = 1 + -1 + 7u Combine like terms: 1 + -1 = 0 0 + 8u = 1 + -1 + 7u 8u = 1 + -1 + 7u Combine like terms: 1 + -1 = 0 8u = 0 + 7u 8u = 7u Solving 8u = 7u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-7u' to each side of the equation. 8u + -7u = 7u + -7u Combine like terms: 8u + -7u = 1u 1u = 7u + -7u Combine like terms: 7u + -7u = 0 1u = 0 Divide each side by '1'. u = 0 Simplifying u = 0
| 4k-2=k-6 | | 15+.25x= | | 3(2x+1)=5(x-4) | | 5(b-6)=3(b+4) | | x+y=4x | | 3(3-x)=15x-27 | | -5y+-5(6-2y)=0 | | 15x-10=-9x+3 | | lny=-3ln(x)+ln(C) | | 4-8x-x=-23 | | 3a^2+25a+50=0 | | 8q-5=5q+3 | | 2y+y-.5=23.5 | | 11-9=-23 | | X+6*4=126 | | 8x=4x-6 | | .4x^2+.2=x | | x-6-7=26(x-7) | | -8x-x=99 | | 6n+2=n+8 | | 2(9c-6)=14 | | -4m-2=82 | | -8(n-7)+3(n-3)=41 | | (9x+y)+(3x+2y)=180 | | -8(n-7)+3(n-3)=31 | | 64=8w-8 | | 2N+7(9N+10)= | | 6+.010x=0.15x+8 | | 4p+2=p+4 | | -5y-5(-62y)=0 | | 13.33+.11x=13.83+.08x | | 14a+5=33 |